2003
DOI: 10.1590/s1516-89132003000300017
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of dextransucrase production by Leuconostoc mesenteroides in fed batch fermentation

Abstract: Fed batch fermentation was carried out for the dextransucrase enzyme production from Leuconostoc mesenteroides and the production was scale-up using oxygen transfer criteriuom. It was found that in 5 L vessel fermentation capacity, the best agitation speed was 225 min-1 and aeration rate was 0.15 vvm, obtaining dextransucrase activity of 127 DSU/mL.. The maximum enzyme production velocity coincide with the maximum growth velocity between 6 and 7 h of fermentation, which confirmed that dextransucrase production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Dols et al, 1996 reported effect of added glucose, fructose and mannitol on dextransucrase and dextran yield from Leuconostoc mesenteroides NRRL B-1299. The aeration conditions were optimized for production and scale up of dextransucrase from Leuconostoc mesenteroides in a bioreactor (Michelena et al, 2003). In our earlier study high glucan production ability of Weissella confusa (Cab3) isolated from fermented cabbage was explored and compared with other lactic acid bacteria (Shukla and Goyal, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dols et al, 1996 reported effect of added glucose, fructose and mannitol on dextransucrase and dextran yield from Leuconostoc mesenteroides NRRL B-1299. The aeration conditions were optimized for production and scale up of dextransucrase from Leuconostoc mesenteroides in a bioreactor (Michelena et al, 2003). In our earlier study high glucan production ability of Weissella confusa (Cab3) isolated from fermented cabbage was explored and compared with other lactic acid bacteria (Shukla and Goyal, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, L. mesenteroides AA1 also produces maximum dextransucrase at 08 hours of fermentation period (Aman et al, 2012). Dextransucrase from L. mesenteroides B/110-1-1 achieved maximum growth rate and enzyme titer between 6 to 7 hours of fermentation (Michelena et al, 2003). Optimum temperature was also observed by incubating the microbes at different temperatures (20°C, 25°C and 30°C).…”
Section: Discussionmentioning
confidence: 90%
“…The values of K L a for 1.0 vvm at 300 rpm, 0.5 vvm at 450 rpm and 1.0 vvm at 600 rpm were 0.18 min -1 , 0.28 min -1 and 0.29 min -1 respectively. The fermentation kinetics of Leuconostoc mesenteroides in a 5 L bioreactor for the production of dextransucrase was studied and K L a obtained was 30.85 h -1 at 0.15 vvm aeration rate and 225 rpm [31]. In case of ß-glucuronidase production by recombinant E. coli, highest enzyme production was obtained at 300 rpm agitation and 2 vvm aeration having K L a value 1.686 h -1 [32].…”
Section: Determination Of Volumetric Oxygen Transfer Coefficient (K L A)mentioning
confidence: 99%